Cryptosporidiosis in Birds - Da Cruz Panegossi, Mariele Fernanda [UNESP]; Fukumori, Felipe Yoshio [UNESP]; Nagata, Walter Bertequini [UNESP]; Ferrari, Elís Domingos [UNESP]; Nakamura, Alex Akira [UNESP]; Inácio, Sandra Valéria [UNESP]; Oliveira, Bruno César Miranda [UNESP]; Viol, Milena Araúz [UNESP]; Gomes, Jancarlo Ferreira; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2020)
Cryptosporidiosis has a worldwide distribution and can affect animals and humans, especially young or immunosuppressed hosts. In birds, this disease has been reported to cause clinical symptoms ranging from diarrhea and weight loss and can lead to death in immunocompromised individuals. Infection occurs when Cryptosporidium spp. oocysts are ingested by a susceptible host. These evolutionary structures are highly resistant to the environment and survive at 20° C for up to six months. Currently, some bird species are considered pets and are found in many public places like garden centers. Due to the close relationship with humans, the disease in question has a great importance to the public health. The purpose of this chapter will address the key clinical, epidemiological and diagnostic methods for this disease.